Penanganan Pasien Covid-19 Pada Rumah Sakit di Indonesia - Fitri Sherida Mahayana; Chriswardani Suryawati; Farid Agushybana (Politeknik Negeri Jember, 2020)
The pre-hospital treatment mechanism is carried out through stopping transmission by educating the public, keeping physical distance when communicating, staying at home, wearing masks, isolating oneself, and implementing Large-Scale Social Restrictions (SPBS). The main goal is of course to break the chain of transmission of Covid-19. The research method used is library research, namely research data based on indexed previous research journals, both national and international. This first mechanism is strengthened by conducting contact tracing of positive confirmation cases. Its success really depends on public participation in addressing the Covid-19 problem, especially by following government regulations. The treatment mechanism in the hospital is carried out by maximizing the services provided to patients, especially Covid-19 patients. Ensure patients get the best service and nurses who are safe from the possibility of contracting Covid-19 from patients. Suggestions to cut the chain of covid-19 transmission from the hospital, namely people with Covid-19 infection will be quarantined in a special room as long as there is no vaccine. This need for quarantine is carried out to make it easier for medical personnel to monitor the condition of patients, as well as to prevent transmission of Covid-19 to other people, including medical personnel who are in charge of caring for them. If a Covid-19 sufferer with mild symptoms, such as a fever below 38 degrees Celsius, does not experience acute respiratory problems, and can still carry out normal activities, can self-quarantine or self-quarantine at home.